A Proposed Agile Based Supply Chain Model for Poultry Based Products in India - Nallusamy , S.; Rekha, R. Suganthini; Balakannan, K.; Chakraborty, P.S.; Majumdar, Gautam (International Journal of Poultry Science, 2014)
The poultry industry in India represents a major success story. With rapidly changing lifestyles, affluent culture and a conscious need for general wellness, Indian consumers are now opting for a more protein-rich diet. From a plot scheme, it has made a quantum leap to become as a dynamic industry. The present decade promises to exploit value added products and the global trade avenue. This paper explores the existing supply chain model of poultry-based products in India. The study is focused on two contexts: the issues faced by poultry farmers in selling the products and retailers’ perspective on the other end. In the current Supply Chain model there is no transparency between the stakeholders which leads to high yield losses, increase in price and uncertainty in the supply and demand analysis. Poultry farmers are paid very less for their product whereas consumers pay huge amount for the same product and there is a lack of technology and financial support for the poultry producers. In our proposed model, we introduce "Agile Based Supply Chain Model for the Poultry Based Products" which will integrate and increase the transparency among the stakeholders in the supply chain and eliminate the mediators and meet out the market demand. Poultry farmers details are updated in the e-commerce platform and these details are transferred to the retailers by the agile team. Support group for poultry farmers and retailers are the two ends of Supply Chain coordinated by agile team.